Radial flow tubular membrane bioreactor for enhanced enzymatic hydrolysis of lignocellulosic waste biomass. (1st June 2023) - Al-Mardeai, Saleha; Elnajjar, Emad; Hashaikeh, Raed; Kruczek, Boguslaw; Van der Bruggen, Bart; Al-Zuhair, Sulaiman
Highlights: Tubular membrane bioreactor was tested for simultaneous product separation. The design allowed handling high solid loadings with minimized mixing problems. Substrate inhibition was encountered due to the structural nature of the biomass. Increasing flowrate from 0.4 to 1.2 mL/min increased the yield up to 42.7 % A model was developed considering product separation and biomass structural changes. Abstract: A tubular membrane bioreactor was used for enhanced enzymatic hydrolysis of waste biomass, palm date seeds. The bioreactor successfully handled high solid loadings with effective simultaneous product removal. The effects of substrate concentrations, 14.3, 21.4, and 39.6 g/L, and water flowrates, 0.4, 0.8, and 1.2 mL/min, on the production of total reducing sugars were examined. At substrate concentration of 21.4 g/L, the total reducing sugars yield increased from 28.9 % to 42.7 % after 8 h as the water flowrate increased from 0.4 to 1.2 mL/min. Substrate inhibition was observed at the highest tested substrate concentration of 39.6 g/L. A dynamic model was developed to describe the designed bioreactor, accounting for the simultaneous product separation and the dynamic changes in substrate structure. The nonhydrolyzable substrate fraction parameter was found to significantly affect the model prediction. The novel membrane bioreactor and the developed model enable the industrial valorization of lignocellulosic biomass for bioethanol production.